S#!%house [videorecording (DVD)] - Raiff, Cooper; Raiff, Cooper; Raiff, Cooper; Gelula, Dylan, 1994-; Landecker, Amy, 1969-; Miller, Logan, 1992- (MPI Home Video, 2021)
When a homesick college freshman attends a party, he spends the night with his sophomore RA.